OGAS: Omni-directional Glider Assisted Scheme for autonomous deployment of sensor nodes in open area wireless sensor network. (January 2023) - Sharma, Vikrant; Vats, Satvik; Arora, D.; Singh, Karan; Prabuwono, Anton Satria; Alzaidi, Mohammed S.; Ahmadian, Ali
Abstract: Wireless Sensor Network (WSN) is built with the wireless interconnection of Sensor Nodes (SNs) generally deployed to monitor the changes within the environment of hostile, rugged, and unreachable target regions. The optimal placement of SNs is very important for the efficient and effective operation of any WSN. Unlike small and reachable regions, the deployment of the SNs in large-scale regions (e.g., forest regions, nuclear radiation affected regions, international border regions, natural calamity affected regions, etc.) is substantially challenging. Present paper deals with an autonomous air-bone scheme for the precise placement of SNs in such large-scale regions. It uses an Omni-directional Circular Glider (OCG) per SN. After being aerially dropped, SN pilots the OCG to glide itself to the predetermined locations (PL) within a target region. The major advantage of using OCG is its capability to quickly update the direction, during the flight (with turning radius = 0) toward its PL. The proposed uses a recursive path correction model to maintain the orientation of the gliding SN towards the PL. The simulation results, and the hardware implementation, indicate that the proposed model is effectively operational in the environmental winds. It is time-efficient and more accurate in the deployment of the SNs in comparison to existing state of art SN deployment models.